A method for preparing a sulfided hydrocracking catalyst
By introducing multifunctional complexing agent and microwave drying technology, equipment corrosion, safety hazards and difficulty in vulcanizing active metals during the vulcanization of hydrocracking catalysts are solved, and efficient and simple vulcanization catalysts are prepared, which improves the performance of the catalyst and Product quality.
Patent Information
- Application Number
- CN202211706670.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-31
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-12-31
AI Technical Summary
The vulcanization process of existing hydrocracking catalysts has problems such as equipment corrosion, safety hazards, high costs, environmental pollution and difficulty in vulcanizing active metals, resulting in a decrease in catalyst activity and selectivity.
Using multifunctional complexing agent combined with hot impregnation, molecular sieve, amorphous silicon aluminum, adhesive, microwave sensitizer and dispersant, high-efficiency and simple vulcanization hydrogenation are prepared through ultrasonic dispersion and microwave drying at different frequencies. Cracking catalyst ensures uniform dispersion and good synergy of active metals.
It realizes efficient and simple catalyst preparation, improves the utilization rate of active metals and the performance of catalysts, is suitable for handling various oil products, and improves product quality and selectivity.
Smart Images

Figure BDA0004033100550000051
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a sulfidation type hydrocracking catalyst. Background Art
[0002] In recent years, with the decreasing oil reserves, the rising international oil prices, and the increasingly serious trend of heavy and inferior crude oil, the market demand for high-quality middle distillate products has continued to increase. Therefore, it is particularly important to increase the production of middle distillates, improve the diesel-gasoline ratio, and improve this supply-demand contradiction. The key to solving this contradiction lies in the development of middle distillate type hydrocracking catalysts with high selectivity. At present, most of the metal active components of industrial hydrocracking catalysts exist in the form of oxides, and in actual use, the active metal oxides on the catalyst need to be converted into sulfides. Therefore, the catalyst needs to be sulfurized or pre-sulfurized before use.
[0003] Conventional catalyst sulfidation methods use "in-situ" sulfidation, which means first loading the oxidized catalyst into the hydrogenation reactor, and then introducing hydrogen and sulfiding agents into the reactor for presulfidation during the continuous heating process. This method brings the following problems: (1) Special presulfidation equipment must be set up on the hydrogenation unit; (2) The sulfiding agent added during the sulfidation process and the water and hydrogen sulfide generated by the reaction can easily cause corrosion of the high-pressure reactor and related equipment, causing equipment damage and safety hazards; (3) The sulfidation process is relatively long, delaying the start-up time. (4) The sulfiding agent used is flammable and toxic, causing environmental pollution during the sulfidation process; (5) The cost of in-situ presulfidation is relatively high.
[0004] To this end, a simple, efficient, pollution-free and low-cost off-site presulfurization technology (or "ex-situ" presulfurization) is developed, which transfers the presulfurization of the catalyst to a special sulfidation reaction device or prepares the catalyst in a sulfided state, so that the catalyst can be loaded into the hydrogenation reactor and used without further sulfidation. This technology has become the development trend of hydrocracking catalyst preparation technology in recent years.
[0005] At present, there are two main technical routes for the publicly reported "ex situ" presulfurization technology of hydrocracking catalysts:
[0006] (1) The first technical route is to first introduce the sulfiding agent into the voids of the oxidized hydrocracking catalyst by sublimation, melting or impregnation, then pre-sulfurize the catalyst part by heating in the presence of an inert gas, and finally load the catalyst into a hydrogenation reactor, and complete the pre-sulfurization of the catalyst in the presence of hydrogen during the start-up heating process;
[0007] (2) The second technical route is to complete the presulfurization of the catalyst in a special presulfurization device in the presence of hydrogen and hydrogen sulfide or an easily decomposable organic sulfiding agent, and then passivate it with oxygen-containing gas to produce a non-spontaneous presulfurized catalyst.
[0008] CN85107953 discloses a method for treating a hydrogenation catalyst, which mainly comprises firstly treating a hydrocracking catalyst by impregnating elemental sulfur and a plurality of organic polysulfides dissolved and diluted with petroleum solvent at 50-150°C, then treating the catalyst at a temperature below 275°C in a hydrogen-free atmosphere, sulfiding the active metal oxide, and finally activating the catalyst at a temperature above 275°C in the presence of hydrogen. CN91101805.7 discloses a method for incorporating sulfur into the pores of a hydrocarbon treatment catalyst, which is characterized in that the catalyst is first treated with a solvent-diluted sulfiding agent, and then sulfided at a temperature above 250°C in the presence of water vapor. The sulfiding agent used is composed of elemental sulfur and an organic sulfur compound that is easily decomposed into hydrogen sulfide in the presence of hydrogen, and the solvent used is a solvent oil containing an olefin fraction or a vegetable oil. US 6,365,542 discloses a method for ex situ sulfurization of a hydrocracking catalyst, which is characterized in that the catalyst is first treated with an oil containing elemental sulfur and olefins at 100-120° C., and then treated with an inert gas at a temperature of 100-300° C. US 6,417,134 discloses an ex situ presulfurization method for a hydrotreating catalyst, which is characterized in that the catalyst is first impregnated with elemental sulfur, organic sulfide, organic polysulfide, olefin-containing oil, and olefin-containing components diluted with a solvent at a temperature of 300° C., and then treated with hydrogen at a temperature of 250-600° C., and finally passivated with an oxygen-containing gas. The above methods all pre-sulfurize the ready-made oxidized catalysts, which have the following shortcomings in the preparation process: the oxides of the active metals Mo, W, Co, Ni of the hydrocracking catalyst, MoO3, WO3, CoO, NiO, have strong interactions with the carrier surface, making the sulfurization of the active metal components difficult and incomplete, reducing the hydrogenation activity of the catalyst, and causing serious environmental pollution during the sulfurization process.
[0009] CN200410039449.5 discloses a method for preparing a sulfidation catalyst, which is to load soluble thiomolybdenum (tungstate) acid salt and Co (Ni) atoms onto the carrier of the catalyst in steps or in one step by means of isovolumetric impregnation, and to heat-treat in an inert gas, thereby preparing a sulfidation catalyst loaded with metal sulfide. Since thiomolybdenum acid salt and thiotungstate acid salt are insoluble in water, it is necessary to add an organic solvent to prepare the solution, and the preparation process is complicated and is not suitable for large-scale industrial production. In addition, the method is in the high temperature treatment process, due to the volatilization of the organic solvent, the interaction between the hydrogenation component and the carrier is strengthened, the sulfidation of the catalyst is affected, the degree of sulfidation is relatively low, and the activity and selectivity of the catalyst decrease.
[0010] Petroleum Refining and Chemical Industry (2011, 42(6): 50-56) studied the effect of calcination temperature on the reaction performance of sulfur-containing precursor hydrocracking catalysts. Ammonium thiomolybdate and nickel nitrate were loaded on a catalyst carrier by kneading and heated in an inert gas to obtain a sulfur-containing metal sulfide sulfide catalyst. This method is simple in process and has a high degree of sulfurization, so that the prepared sulfurized hydrocracking catalyst has high activity and selectivity. However, due to the poor uniformity of metal dispersion and low metal utilization of the catalyst prepared by the kneading method, the activity of the catalyst and product properties are affected. Summary of the invention
[0011] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art. By introducing a multifunctional complexing agent, combining hot impregnation, molecular sieves, amorphous silicon aluminum, adhesives, microwave sensitizers and dispersant mixing, ultrasonic dispersion and microwave drying treatment of different frequencies under nitrogen protection, a method for preparing a sulfided hydrocracking catalyst with high efficiency and simplicity, uniform dispersion of active metals, good synergy between different active metals, high effective utilization rate of active metals and excellent performance is provided.
[0012] The invention discloses a method for preparing a sulfurized hydrocracking catalyst. The method comprises: firstly mixing ammonium dithiocarbamate, nickel salt and / or cobalt salt, ammonium citrate and a certain amount of deionized water, heating and stirring, then adding ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate, mixing the obtained sulfur-containing composite active metal precursor impregnation liquid with molecular sieve, amorphous silicon aluminum, adhesive, microwave sensitizer and dispersant at a temperature of 50-90 DEG C, then ultrasonically dispersing, beating, kneading and extruding, and then drying with microwaves with a radiation frequency of 840 MHz and a microwave drying temperature of 100-120 DEG C under nitrogen protection, and then drying with microwaves with a radiation frequency of 2450 MHz and a microwave drying temperature of 350-600 DEG C to obtain a sulfurized hydrocracking catalyst; wherein the molar amount of the ammonium dithiocarbamate used is 50%-300% of the molar amount of the nickel salt and / or the cobalt salt, preferably 100%-150%.
[0013] In the method for preparing the sulfided hydrocracking catalyst of the present invention, the nickel salt and / or cobalt salt is preferably selected from one or more of basic carbonates, nitrates and acetates, and more preferably basic carbonates.
[0014] In the preparation method of the sulfided hydrocracking catalyst of the present invention, the molecular sieve can preferably be one or more of ZSM-5 molecular sieve, Y-type molecular sieve, SAPO molecular sieve, β molecular sieve and MCM-41 mesoporous molecular sieve, and the binder can be one or more of aluminum sol, silica sol, aluminum silicate and silica-alumina gel.
[0015] In the method for preparing the sulfided hydrocracking catalyst of the present invention, the microwave sensitizer can preferably be one or more of Fenton's reagent, activated carbon, graphite, conductive carbon black, semi-conductive carbon black and carbon fiber sensitizer.
[0016] In the preparation method of the sulfurized hydrocracking catalyst of the present invention, the dispersant is preferably one or more of alkylamide compounds, polycarboxylic acids, oligomers composed of polycarboxylic acids and polyamines, triethylhexyl phosphoric acid, alkyl sulfates, alkyl sulfonates, methyl amyl alcohol, cellulose derivatives, polyacrylamide, guar gum, fatty acid polyethylene glycol esters, silicates, polyethylene wax, oxidized polyethylene wax, polyethylene glycol, polyvinyl alcohol, polypropylene alcohol, methyl cellulose, carboxymethyl cellulose, isopropanol, sec-butyl alcohol, levulinic acid esters, hydrolyzed polymaleic anhydride (HPMA), ethylene-acrylic acid copolymers, ethylene-vinyl acetate copolymers, metal salts of higher fatty acids, fatty acid compounds, aliphatic amide compounds, ester compounds, paraffin, polyurethane, fatty acid glyceride, fatty acid sorbitan, Tween, fatty alcohol polyoxyethylene ethers, alkylphenol polyoxyethylene ethers and acrylic polymers (such as LBD-1 dispersant), and the amount used is 1wt% to 20wt% of the weight of the carrier component.
[0017] In the method for preparing the sulfided hydrocracking catalyst of the present invention, the ultrasonic time is preferably 5 to 30 minutes.
[0018] In the method for preparing the sulfided hydrocracking catalyst of the present invention, it is preferred that the 840 MHz and 2450 MHz microwave drying times are 10 to 30 minutes and 20 to 120 minutes, respectively.
[0019] In the preparation method of the sulfided hydrocracking catalyst of the present invention, it is preferred that the sulfided hydrocracking catalyst contains 5wt% to 30wt% of molybdenum and / or tungsten as elements, and 1wt% to 10wt% of cobalt and / or nickel as elements, based on the weight of the final catalyst.
[0020] The present invention further provides a sulfided hydrocracking catalyst prepared by the above preparation method.
[0021] Compared with the prior art, the preparation method of the present invention has the following beneficial effects: by introducing a multifunctional complexing agent, combining hot impregnation, molecular sieves, amorphous silicon aluminum, adhesives, microwave sensitizers and dispersant mixing, ultrasonic dispersion and microwave drying treatment of different frequencies under nitrogen protection, the preparation method of the present invention has the advantages of high efficiency and simplicity, uniform dispersion of active metals, good synergy of different active metals and high effective utilization rate of active metals, and the prepared sulfided hydrocracking catalyst has the advantages of excellent performance.
[0022] The sulfided hydrocracking catalyst prepared by the method of the present invention is mainly used in the hydrocracking process and is suitable for treating one or more of various oil products such as vacuum gas oil, thermal cracking gas oil, catalytic cracking gas oil, catalytic cracking circulating oil, coking gas oil, deasphalted oil, etc. The raw material is usually hydrocarbons with a boiling point of 180 to 700°C, and the nitrogen content can be 10 to 5000 μg / g. DETAILED DESCRIPTION
[0023] The technical features of the present invention are described in detail below with specific embodiments, but the embodiments do not limit the protection scope of the present invention.
[0024] The specific preparation steps of the present invention are as follows: firstly, ammonium dithiocarbamate, nickel salt and / or cobalt salt, ammonium citrate and a certain amount of deionized water are mixed, heated and stirred, then ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate are added, the obtained sulfur-containing composite active metal precursor impregnation solution is mixed with molecular sieve, amorphous silicon aluminum, adhesive, microwave sensitizer and dispersant at a temperature of 50°C to 90°C, then ultrasonically dispersed, slurried, kneaded and extruded, and then under nitrogen protection, firstly dried with microwaves with a radiation frequency of 840 MHz and a microwave drying temperature of 100 to 120°C, and then dried with microwaves with a radiation frequency of 2450 MHz and a microwave drying temperature of 350-600°C to obtain a sulfurized hydrocracking catalyst.
[0025] Embodiment 1:
[0026] 15 g of ammonium dithiocarbamate, 8 g of basic nickel carbonate, 3 g of ammonium citrate and 40 g of deionized water were mixed, heated and stirred at 90° C., and then 30 g of ammonium tetrathiomolybdate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 40 g of Y-type molecular sieve, 25 g of amorphous silica-alumina, 100 g of aluminum sol (solid content mass fraction was 35%), 1 g of activated carbon and 1 g of carboxymethyl cellulose at a temperature of 90° C., and then ultrasonically dispersed for 5 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, first dried with a microwave with a radiation frequency of 840 MHz, a microwave drying temperature of 100° C., and a drying time of 30 minutes, and then dried with a microwave with a radiation frequency of 2450 MHz, a microwave drying temperature of 450° C., and a drying time of 50 minutes to obtain a sulfurized hydrocracking catalyst A.
[0027] Embodiment 2:
[0028] 3 g of ammonium dithiocarbamate, 6 g of nickel nitrate, 3 g of nickel acetate, 2 g of ammonium citrate and 40 g of deionized water were mixed, heated and stirred at 80° C., and then 30 g of ammonium tetrathiotungstate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 30 g of Y-type molecular sieve, 10 g of β-type molecular sieve, 25 g of amorphous silica-alumina, 100 g of aluminum sol (solid content mass fraction was 35%), 0.5 g of Fenton's reagent and 0.5 g of polyethylene glycol at 80° C., and then ultrasonically dispersed for 10 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, first dried with a microwave with a radiation frequency of 840 MHz, a microwave drying temperature of 120° C., and a drying time of 10 minutes, and then dried with a microwave with a radiation frequency of 2450 MHz, a microwave drying temperature of 600° C., and a drying time of 20 minutes to obtain a sulfurized hydrocracking catalyst B.
[0029] Embodiment 3:
[0030] 4.5 g of ammonium dithiocarbamate, 4.5 g of nickel nitrate, 3 g of nickel acetate, 1 g of ammonium citrate and 40 g of deionized water were mixed, heated and stirred at 70°C, and then 20 g of ammonium tetrathiomolybdate and 10 g of ammonium tetrathiotungstate were added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 50 g of Y-type molecular sieve, 15 g of SAPO molecular sieve, 100 g of silica sol (solid content mass fraction is 35%), 0.5 g of graphite and 0.5 g of Tween at 70°C, and then ultrasonically dispersed for 15 minutes, beaten, kneaded, extruded, and then under nitrogen protection, first dried with microwaves with a radiation frequency of 840 MHz, a microwave drying temperature of 110°C, and a drying time of 15 minutes, and then dried with microwaves with a radiation frequency of 2450 MHz, a microwave drying temperature of 350°C, and a drying time of 120 minutes to obtain a sulfurized hydrocracking catalyst C.
[0031] Embodiment 4:
[0032] 6 grams of ammonium dithiocarbamate, 6 grams of nickel nitrate, 3 grams of cobalt nitrate, 5 grams of ammonium citrate and 40 grams of deionized water were mixed, heated and stirred at 50°C, and then 30 grams of ammonium tetrathiomolybdate were added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 45 grams of Y-type molecular sieve, 20 grams of MCM-41 mesoporous molecular sieve, 60 grams of aluminum sol (solid content mass fraction of 35%), 40 grams of silica sol (solid content mass fraction of 35%), 0.5 grams of carbon fiber sensitizer and 0.5 grams of gul gum at a temperature of 50°C, and then ultrasonically dispersed for 30 minutes, beaten, kneaded, extruded, and then under nitrogen protection, first dried with a microwave with a radiation frequency of 840MHz, a microwave drying temperature of 100°C, and a drying time of 25 minutes, and then with a microwave radiation frequency of 2450MHz, a microwave drying temperature of 500°C, and a drying time of 60 minutes to obtain a sulfurized hydrocracking catalyst D. Comparative Example 1:
[0033] 6 g of nickel nitrate, 3 g of cobalt nitrate, 3 g of citric acid and 40 g of deionized water were mixed, stirred at 30°C for 1 hour, and then 30 g of ammonium tetrathiomolybdate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 45 g of Y-type molecular sieve, 20 g of MCM-41 mesoporous molecular sieve, 60 g of aluminum sol (solid content mass fraction of 35%), and 40 g of silica sol (solid content mass fraction of 35%) at 30°C under nitrogen protection, and calcined at 500°C for 5 hours to obtain a hydrocracking catalyst E.
[0034] Table 1 Physicochemical properties of the catalysts obtained in the examples and comparative examples
[0035]
[0036] It can be seen from Table 1 that the specific surface area, pore volume and strength of the sulfided hydrocracking catalyst prepared according to the present invention are superior to those of the sulfided hydrocracking catalyst prepared according to the conventional method.
[0037] The activity evaluation test of the above-mentioned sulfided hydrocracking catalyst A, sulfided hydrocracking catalyst B, sulfided hydrocracking catalyst C, sulfided hydrocracking catalyst D and hydrocracking catalyst E of the present invention was carried out on a 100 mL small-scale hydrogenation device. The properties of the raw oil used are shown in Table 2. The evaluation conditions are: hydrogen partial pressure of 14 MPa, hydrogen-oil volume ratio of 1200:1, reaction temperature of 370°C, liquid hourly volume space velocity of 1.2 h -1 The catalyst evaluation results are shown in Table 3.
[0038] Table 2 Properties of the raw oil used for evaluation
[0039] name Crude oil <![CDATA[Density (20 °C), g / cm 3 > 0.9238 Distillation range / ℃ IBP / 10% / 50% / 90% / 95% / EBP 309 / 426 / 474 / 526 / 537 / 553 Sulfur content, μg / g 13423 Nitrogen content, μg / g 1325 BMCI value 43
[0040] Table 3 Catalyst activity evaluation results
[0041] catalyst Catalyst A Catalyst B Catalyst C Catalyst D Catalyst E Nitrogen content of refined oil, μg / g 5 8 7 9 13 Selectivity of crude oil, % 89.1 87.8 88.7 81.2 78.5 Main product properties Aromatic potential of naphtha, wt% 64.2 63.8 64.5 61.2 59.8 Smoke point of jet fuel, mm 34 31 33 27 24 Cetane number of diesel 69 65 68 59 56 BMCI of tail oil 5.7 6.1 5.9 8.2 8.7
[0042] The evaluation results show that, compared with the hydrocracking catalyst E prepared by the conventional method, the sulfided hydrocracking catalyst prepared according to the present invention has the characteristics of good comprehensive performance, strong nitrogen resistance and high activity, and can effectively improve product distribution and enhance product quality.
[0043] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the invention may be modified or replaced by equivalents without departing from the scope of the technical solutions of the present invention, which should all be covered by the scope of the claims of the present invention.
Claims
1. A method for preparing a sulfided hydrocracking catalyst, characterized in that: The preparation method comprises: firstly mixing ammonium dithiocarbamate, nickel salt and / or cobalt salt, ammonium citrate and a certain amount of deionized water, heating and stirring, then adding ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate, mixing the obtained sulfur-containing composite active metal precursor impregnation solution with molecular sieve, amorphous silicon aluminum, adhesive, microwave sensitizer and dispersant at a temperature of 50°C to 90°C, then ultrasonically dispersing, beating, kneading and extruding, and then under nitrogen protection, first drying with microwaves having a radiation frequency of 840 MHz and a microwave drying temperature of 100 to 120°C, and then drying with microwaves having a radiation frequency of 2450 MHz and a microwave drying temperature of 350-600°C to obtain a sulfurized hydrocracking catalyst, wherein the molar amount of the ammonium dithiocarbamate used is 50% to 300% of the molar amount of the nickel salt and / or the cobalt salt.
2. The method for preparing a sulfided hydrocracking catalyst according to claim 1, characterized in that: The molar amount of the ammonium dithiocarbamate used is 100% to 150% of the molar amount of the nickel salt and / or the cobalt salt.
3. The method for preparing a sulfided hydrocracking catalyst according to claim 1, characterized in that: The nickel salt and / or cobalt salt is selected from one or more of basic carbonate, nitrate and acetate.
4. The method for preparing a sulfided hydrocracking catalyst according to claim 1, characterized in that: The molecular sieve is one or more of ZSM-5 molecular sieve, Y-type molecular sieve, SAPO molecular sieve, β molecular sieve and MCM-41 mesoporous molecular sieve, and the binder is one or more of aluminum sol and silica sol.
5. The method for preparing a sulfided hydrocracking catalyst according to claim 1, characterized in that: The microwave sensitizer is one or more of Fenton's reagent, activated carbon, graphite, conductive carbon black, semi-conductive carbon black and carbon fiber sensitizer.
6. The method for preparing a sulfided hydrocracking catalyst according to claim 1, characterized in that: The dispersant is one or more of alkylamide compounds, polycarboxylic acids, oligomers composed of polycarboxylic acids and polyamines, triethylhexyl phosphoric acid, alkyl sulfates, alkyl sulfonates, methyl amyl alcohol, cellulose derivatives, gum guar, silicates, polyethylene wax, oxidized polyethylene wax, polyethylene glycol, polyvinyl alcohol, polypropylene alcohol, isopropanol, sec-butyl alcohol, hydrolyzed polymaleic anhydride, ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer, metal salts of higher fatty acids, fatty acid compounds, ester compounds, paraffin, Tween, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and acrylic polymers, and the amount used is 1wt%~20wt% of the weight of the carrier component.
7. The method for preparing a sulfided hydrocracking catalyst according to claim 1, characterized in that: The ultrasonic time is 5 to 30 minutes.
8. The method for preparing a sulfided hydrocracking catalyst according to claim 1, characterized in that: The 840MHz and 2450MHz microwave drying times are 10 to 30 minutes and 20 to 120 minutes respectively.
9. The method for preparing a sulfided hydrocracking catalyst according to claim 1, characterized in that: The sulfided hydrocracking catalyst contains 5wt% to 30wt% of molybdenum and / or tungsten, and 1wt% to 10wt% of cobalt and / or nickel, based on the weight of the final catalyst.
10. A sulfided hydrocracking catalyst prepared by the preparation method according to any one of claims 1 to 9.
